A new Bufo (Anura: Bufonidae) from the peat swamps of Selangor, West Malaysia - Das, I.; Lim, Kelvin K. P. (National University of Singapore, 2001)
A new species of the genus Bufo is described from the peat swamps of North Selangor, West Malaysia. B. kumquat, new species, is a member of the B. biporcatus group (sensu Inger, 1972), differentiable from its members in showing the following combination of characters: small adult male body size (SVL to 27.5 mm); first two fingers subequal; tip of toe In reaches median subarticular tubercle of toe IV; preparatoid crest absent; internarial distance greater than tympanum diameter; metatarsal tubercle elongate; subarticular tubercle not enlarged; parotoid gland elongated; outer carpal tubercle oval; breeding males lacking nuptial pads; tympanum pigmented; vocal sac yellow with scattered dark grey pigmentation; flanks with scattered dark pigmentation, lacking a distinct dark band; and dorsum pale yellow with scattered dark pigments.